Northward migration dynamics of skipjack tuna (Katsuwonus pelamis) associated with the lower thermal limit in the western Pacific Ocean. (July 2019) - Kiyofuji, H.; Aoki, Y.; Kinoshita, J.; Okamoto, S.; Masujima, M.; Matsumoto, T.; Fujioka, K.; Ogata, R.; Nakao, T.; Sugimoto, N.; Kitagawa, T.
Highlights: We documented three major migration routes of skipjack tuna from subtropical to temperate waters off Japan. The 18 °C isotherm is an appropriate indicator for the lowest thermal limit of skipjack tuna distribution. Horizontal and vertical habitat of skipjack tuna are strongly driven by the 18 °C thermal limit. The 18 °C isotherm limited skipjack tuna to surface waters in the northernmost part of their habitat. Abstract: A new and comprehensive migration route of skipjack tuna, Katsuwonus pelamis, in the western Pacific Ocean was observed from the results of a large scale tagging project conducted from 2010 to 2016. Skipjack were implanted with archival tags in the peritoneal cavity and released from a subtropical area (STA), the Nansei Islands (NSI) and the Kuroshio Extension Area (KEA). Individuals released around the NSI displayed strong residency in that area. On the other hand, individuals released around the STA and KEA demonstrated seasonal northward movements. Three major potential routes were observed with strong skipjack residency along; (i) the Kuroshio in the NSI, and with seasonal northward movements along (ii) the Kyushu-Palau ridge and (iii) the Izu-Ogasawara Islands. During northward migration, the skipjack experienced several specific physical oceanographic structures such as the Kuroshio recirculation area (subtropical mode waters), the Kuroshio Current near the coast of Japan, the Kuroshio Extension and the Kuroshio–Oyashio transition area. However, during their journey the skipjack did not enter water with temperatures of ≤18 °C (defined as the lower thermal limit). Furthermore, the depth of the lower thermal limit is progressively shoaled at higher latitudes due to the distribution of colder water masses below 18 °C, which further limits the vertical distribution of skipjack. Our findings are the first fishery-independent observations on the degree of horizontal and vertical habitat of skipjack tuna in the western Pacific Ocean, which can be strongly driven by behavioural responses to the lower thermal limit.